Individual Internship Project: Proposal for improving the operations at S. K. Products (Bangalore) Private Limited - Kondayath, Anand (2009)
The report covers a detailed description about the operations of S. K. Products (Bangalore) Private Limited (SKPB), a business concern in India, which is into manufacturing of polypropylene multifilament yarn and narrow woven fabrics. The report emanates with an overview of the company and later on provides an overview of the industry it is a part of. Along with the company and industry overview, the introduction chapter puts light on the research area focused and the purpose of this study. Following the introduction, the literature review section provides an abridgment of the key research that has been undertaken by various academics on topics that is considered relevant to the research study. The next chapter is research methodology, which explains about the approach used to conduct the study. The chapter gives a detailed description about how the author worked with the company’s team to extract information and how the same was congregated with his latest academic experience.